THE DETERMINANTS OF SAVINGS IN INDONESIAN HOUSEHOLDS (USING IFLS DATA) - Syofriza Syofyan; Mahjus Ekananda (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
The growing concern among researchers and analysts with regard to the decline in savings amounts is not without intention, interest and purpose. As saving is a personal and individual matter, an approach in which people are urged to augment their savings cannot be taken for granted. Yet while everyone has their own unique set of needs, preferences, motives and habits, this research aims to identify the typical factors that determine household saving in Indonesia. The model to test which factors are the most important is saving as a function of income, consumption, demographic status, psychological, institutional, and financial literacy. The respondents were derived from the Indonesian Family Life Survey (IFLS) from periods 2007 and 2014. Using quantile regression, we found income to be the most significant factor for saving in 2007 followed by education attainment, employment status and past saving experience. In 2014, the most influential factors were income, risk preference, employment status, urban/rural location and disincentives for going to the bank. Access to finance may offer the potential to resolve the whole of the financial issue for both sides, the demanders and suppliers of microfinancing, both individually and institutionally